2022
DOI: 10.1002/ijc.34372
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and tolerability of sintilimab plus anlotinib as the second‐line therapy for patients with advanced biliary tract cancers: An open‐label, single‐arm, phase II clinical trial

Abstract: Patients with biliary tract cancer (BTC) were associated with poor prognosis and limited therapeutic options after first-line therapy currently. In this study, we sought to evaluate the feasibility and tolerability of sintilimab plus anlotinib as the second-line treatment for patients with advanced BTC. Eligible patients had histologically confirmed locally advanced unresectable or metastatic BTC and failed after the first-line treatment were recruited. The primary endpoint was overall survival (OS). Simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Two studies with a total of 44 patients evaluated the role of gut microbiota in response to programmed cell death receptor-1 (PD-1) antagonists in patients suffering from CCA [ 52 , 53 ]. Both studies reported the results of patients with advanced-stage disease after failure of first-line treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies with a total of 44 patients evaluated the role of gut microbiota in response to programmed cell death receptor-1 (PD-1) antagonists in patients suffering from CCA [ 52 , 53 ]. Both studies reported the results of patients with advanced-stage disease after failure of first-line treatment.…”
Section: Resultsmentioning
confidence: 99%
“… 29 Anlotinib has been authorized for the treatment of patients diagnosed with acinar soft tissue sarcoma, clear cell sarcoma, and other recurrent advanced soft tissue sarcomas. 30 , 31 After fully informing the patient of their condition, the patient received a combination of sintilimab, anlotinib and paclitaxel albumin every 3 weeks as the initial therapeutic approach following comprehensive discussion and evaluation. Following two cycles of this treatment regimen, the patient’s abdominal CT scan revealed a reduction in liver lesions, as well as significant shrinkage in gallbladder lesions and lymph nodes compared to previous scans.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, compared to nivolumab and toripalimab which were widely used for ECC, patients faced much fewer financial burdens. Additionally, these two PD-1 inhibitors have been proven to be effective and safe in advanced ECC trials ( 36 , 37 ). Third, we did not further evaluate microsatellite instability-high status, mismatch repair protein deficiency, and programmed death-ligand 1 before using the PD-1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%